Comparison of Locoregional versus Extended Locoregional Radiation Volumes for Patients with Nonmetastatic Gastro-esophageal Junction Carcinomas. Issue 3 (March 2015) - Wang, Jingya; Milton, Denái R.; He, Liru; Komaki, Ritsuko; Liao, Zhongxing; Crane, Christopher H.; Minsky, Bruce D.; Thall, Peter F.; Lin, Steven H.
Abstract : Introduction: To delineate an optimal clinical target volume (CTV) for gastroesophageal junction (GEJ) cancers by comparing locoregional versus extended locoregional radiation (RT) volumes. Materials: This retrospective analysis examined 222 patients (111 matched pairs treated with locoregional versus extended locoregional RT) with nonmetastatic GEJ carcinomas treated with concurrent chemoradiation ± surgery. The CTV for locoregional volumes was defined as gross tumor volume + elective coverage of first-echelon nodes and sometimes the celiac axis. The CTV for extended locoregional volumes was defined as gross tumor volume + elective coverage of celiac and splenic (±porta) nodes. Variables used for matching included sex, stage, performance status, histology, receipt of induction chemotherapy, type of concurrent chemotherapy, RT modality, receipt of surgery, type of surgery, and Siewert classification. Regression models stratified by matched pairs were fit to estimate effect of RT volume on clinical endpoints. Results: Adjusting p values for multiple testing, patients treated with extended locoregional versus locoregional RT had increased odds of grade 2+ acute chemoradiation-associated gastrointestinal toxicity (odds ratio: 2.92, adj. p = 0.0447). However, differing RT volumes were not significantly associated with postoperative complication rates, pathologic T-stage, frequency of positive perigastric/regional nodes on surgical specimen, distant-metastases progression-free survival, locoregional progression-free survival, or overall survival (adj. p > 0.05). Of the patients who did ( n = 124) and did not ( n = 72) receive elective celiac RT, two (1.6%) and two patients (2.8%), respectively, relapsed in the celiac nodes. No patients failed in the splenic or porta nodes. Conclusions: Most GEJ cancers can be safely treated without elective inclusion of splenic/porta nodes.